Anxiety and depression among people living in quarantine centers during COVID-19 pandemic: A mixed method study from western Nepal. - Udaya Bahadur B C; Sunil Pokharel; Sabika Munikar; Chetan Nidhi Wagle; Pratik Adhikary; Brish Bahadur Shahi; Chandra Thapa; Ram Prasad Bhandari; Bipin Adhikari; Kanchan Thapa (PLoS ONE)
Background In response to the COVID-19 pandemic, incoming travelers were quarantined at specific centers in Nepal and major checkpoints in Nepal-India border. Nepal adopted a generic public health approaches to control and quarantine returnee migrants, with little attention towards the quality of quarantine facilities and its aftermath, such as the poor mental health of the returnee migrants. The main objective of this study was to explore the status of anxiety and depression, and factors affecting them among returnee migrants living in institutional quarantine centers of western Nepal. Methods A mixed method approach in this study included a quantitative survey and in-depth interviews (IDIs) among respondents in quarantine centers of Karnali province between 21st April and 15th May 2020. Survey questionnaire utilized Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) tools, which were administered among 441 quarantined returnee migrants. IDIs were conducted among 12 participants which included a mix of six quarantined migrants and healthcare workers each from the quarantine centres. Descriptive and inferential analyses were conducted on quantitative data; and thematic analysis was utilized for qualitative data. Results Mild depression (9.1%; 40/441) and anxiety (16.1%; 71/441) was common among respondents followed by moderate depression and anxiety {depression (3.4%; 15/441), anxiety (4.1%; 18/441)} and severe depression and anxiety {depression (1.1%; 5/441), anxiety (0.7%; 3/441)}. Anxiety and depression were independent of their socio-demographic characteristics. Perceived fear of contracting COVID-19, severity and death were prominent among the respondents. Respondents experienced stigma and discrimination in addition to being at the risk of disease and possible loss of employment and financial responsibilities. In addition, poor (quality and access to) health services, and poor living condition at the quarantine centres adversely affected respondents' mental health. Conclusion Depression and anxiety were high among quarantined population and warrants more research. Institutional quarantine centers of Karnali province of Nepal were in poor conditions which adversely impacted mental health of the respondents. Poor resource allocation for health, hygiene and living conditions can be counterproductive to the population quarantined.